Chronological Change of the Clinical Features and Treatment Outcomes for Subarachnoid Hemorrhage in Japan: A Multicenter Retrospective Study - Hiroaki MURAYAMA; Kazuya KANEMARU; Hideyuki YOSHIOKA; Akira FUKAMACHI; Tsuneo SHIMIZU; Tomohiro OMATA; Isao FUKASAWA; Mitsuyasu NAGASAKA; Shin NAKANO; Yasuhiro ASARI; Hiroyuki KINOUCHI (Neurologia Medico-Chirurgica, 2023)
Aneurysmal subarachnoid hemorrhage (SAH) treatment has progressed, and patients are rapidly aging in Japan. Consequently, dynamic changes must have emerged in the clinical practice of SAH. This study aimed to elucidate chronological changes of aneurysmal SAH and the prognostic factors in the previous quarter century in Japan. We conducted a retrospective survey regarding aneurysmal SAH in eight institutions in Japan. The study included 848, 863, and 781 patients in the first (1989-1993), second (1999-2003), and third (2009-2013) periods, respectively. The chronological changes of factors that influenced the poor outcomes and differences between the nonelderly (<75 years) and elderly patients were investigated. Mean age was significantly higher in patients in the third period (61.4 years) than in those in the other two periods (first, 57.8 years; second, 59.5 years). During these periods, the proportion of good outcomes did not change; however, the mortality rate significantly decreased from 19% in the first period to 11% and 9.2% in the second and third periods, respectively. The poor outcome was mainly caused by the significantly higher incidence of systemic complication and procedural complication in the first period and the significantly lower incidence of delayed ischemic neurological deficit in the third period. The elderly patients had significantly poorer clinical outcomes than the nonelderly ones. During the last 25 years, the age of patients with aneurysmal SAH has rapidly increased. The study results may contribute to the improvement of the treatment strategy of SAH in advanced countries with a rapidly aging population.